1992
DOI: 10.1093/ptj/72.10.711
|View full text |Cite
|
Sign up to set email alerts
|

Attribute Dimensions that Distinguish Master and Novice Physical Therapy Clinicians in Orthopedic Settings

Abstract: The purpose of this qualitative case study was to further investigate the work of master and novice clinicians within the practice setting. The sample consisted of three master clinicians and three novice clinicians practicing in orthopedic outpatient physical therapy settings in three different regions of the United States. Data collection by three researchers included observation of each clinician treating at least three patients, audiotaping of all treatment sessions, interviews with clinicians and patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(72 citation statements)
references
References 20 publications
2
69
0
1
Order By: Relevance
“…This finding is consistent with findings from research investigating the clinical reasoning of musculoskeletal physiotherapists (Noll et al, 2001;Thornquist, 2006;Cruz et al, 2012). Practice akin to technical rationality has been considered an attribute of novice healthcare practitioners (Jensen et al, 1990(Jensen et al, , 1992Unsworth, 2001;Smith et al, 2008, Smith et al, 2010, where practice is characterised as being practitioner-centred, emphasising the application of specific factual knowledge and technical skills in a routine predictable manner. In this current study, no relationship between participants' years of clinical experience and their conception of practice was found.…”
Section: Discussionsupporting
confidence: 83%
“…This finding is consistent with findings from research investigating the clinical reasoning of musculoskeletal physiotherapists (Noll et al, 2001;Thornquist, 2006;Cruz et al, 2012). Practice akin to technical rationality has been considered an attribute of novice healthcare practitioners (Jensen et al, 1990(Jensen et al, , 1992Unsworth, 2001;Smith et al, 2008, Smith et al, 2010, where practice is characterised as being practitioner-centred, emphasising the application of specific factual knowledge and technical skills in a routine predictable manner. In this current study, no relationship between participants' years of clinical experience and their conception of practice was found.…”
Section: Discussionsupporting
confidence: 83%
“…All other studies 41,45,47 did not report on the previous experience and skills of therapists. Jensen et al 70 reported that experienced clinicians' knowledge was more extensive in comparison to novice clinicians and that they were more comfortable with their knowledge level. Studies show that physical therapists with higher self-awareness and confidence in their clinical judgement, problem solving skills, and the ability to communicate this to each patient (i.e.…”
mentioning
confidence: 99%
“…Expert practice in physiotherapy has been proposed to involve a combination of knowledge, clinical reasoning, movement and virtues (Jensen et al 2000), whilst "master" or expert practice when compared to novice has been shown to be separated by the ability to use time, develop frameworks, communicate, teach, and predict clinical outcomes (Jensen et al 1992). The musculoskeletal physiotherapy literature surrounding therapists and reasoning suggests that clinicians commonly may generate initial hypotheses and subsequently test them via questioning or physical examination procedures (hypotheticodeductive) in a deductive way from a general presentation resulting to one that is more specific (Jones 1995;Loftus and Smith 2008).…”
Section: Methods Of Reasoningmentioning
confidence: 99%